PRONOUN AS ONE OF COHESIVE DEVICES IN ENGLISH AND INDONESIAN HORTATORY TEXT: A TEXTUAL STUDY - Ifoni Ludji (Academic Journal of Educational Sciences, 2020)
This research aims at analyszing prnouns as cohesive devices in English and Indonesian hortatory text. For compelting this research,the pronoun notion comes up as the fundamental theory. This research is a kind of library research. The result indictaes that English text andIndonesia text needs prnouns to make it be more expressive.